Life Expectancy at Birth and Lifetime Education and Earnings - Hoque, Mohammad Mainul (World Bank, Washington, DC, 2020)
Exploiting cross–birth cohort and cross-country variation from a pool of 188 household surveys from 111 countries, this paper measures how life expectancy at birth affects lifetime education and earnings. On average, individuals add one year of schooling for every 8.3 years of increased life expectancy at birth. Lifetime earnings increase by 1.7 percent per year of added life expectancy at birth. The estimates imply that rising life expectancy at birth explains 75 percent of the increase in average years of schooling worldwide for birth cohorts between 1922 and 1987 and 38 percent of the increase in average gross domestic product per capita in the 20th century.